“Susceptibilidad a deslizamientos mediante el uso de SIG, a escala 1: 10 000, del tramo vial comprendido desde: el redondel del barrio el Plateado hasta el antiguo peaje del cantón Catamayo, provincia de Loja” - Cabrera Malla, Edgar Mauricio (2021)
The present investigation consisted in making a map of susceptibility to landslides at a scale of 1: 10 000, of the road section concerned from the El Plateado neighborhood with coordinates X: 696095.1; Y: 9559711.8 from the city of Loja, up to the old tollbooth of the Catamayo canton with coordinates X: 684849.2; Y: 9559706.7 identifying and characterizing areas susceptible to landslides. For this purpose, we worked with different variables that condition landslides, which were defined according to the author in hierarchical order as follows: Geology, slopes, Geomorphology, coverage and land use, in addition to assist with the analysis of susceptible areas, we worked with two triggering factors which were implemented by the incidence caused in the instability of the terrain, these factors are: precipitation worked in mm/year and annual temperatures in oC. The information collected in the field was processed in ArcGIS 10.3 software using the Spatial Multicriteria Rank Sum Method, which, as mentioned by Estrella, O (2016), is based on the assignment of weights for the variables of the susceptibility map, the same that considers the factors that influence instability by assigning weights or expert criteria, the weights were assigned according to the methodology of Janssen and Van Herwjnen (1994) and the hierarchical order was determined according to the author denoting the following values: Geology (0.29), Slopes (0.24), Geomorphology (0.19), Land cover and land use (0.14), Precipitation (0.10) and Temperature (0.05). A correlation was made between the results obtained in the office and the real conditions of the terrain, making an inventory of landslides, identifying: 6 rotational landslides, distributed along the road section and 8 translational landslides, which like the previous ones were scattered throughout the study area. From the results obtained, 8 landslides are located in high susceptibility zones, and the remaining ones are located in very high susceptibility zones, verifying the effectiveness of the method. As a final result of the application of the Sum of Ranges Method, the landslide susceptibility map was obtained at a scale of 1:10,000, obtaining the following results: of a total of 4,560.01 ha: 88,20 ha, correspond to very low susceptibility occupying 1,93%, 588,10 ha correspond to low susceptibility occupying 12,90%, 1606,47 ha, correspond to medium susceptibility occupying 35,23%, 1909,89 ha, correspond to high susceptibility occupying 41,89%, finally 367,35 ha, which correspond to very high susceptibility occupying 8,05 % . The purpose of the research work is to be used as an adjuvant tool, which can be used to support the decision making process of the different governmental agencies in the elaboration of Land Management Plans, adaptation and/or improvement of roads and the correct spatial disposition of possible human settlements near the area of influence of the study zone. Keywords: Landslide susceptibility, conditioning factors, triggers factors, analytical hierarchies, ArcGIS 10.3, ranges.